Population Pharmacokinetics of Recombinant Factor VIIa in Volunteers Anticoagulated with Acenocoumarol - Girard, Pascal; Nony, Patrice; Erhardtsen, Elisabeth; Delair, Sylvie; Ffrench, Patrick; Dechavanne, Marc; Boissel, Jean-Pierre (Thrombosis and Haemostasis, 1998)
This study establishes a population PK model for FVII clotting activity (FVII:C) after injection of recombinant activated factor VII (rFVIIa) to healthy volunteers. Twenty eight volunteers, anticoagulated with acenocoumarol, received one or two rFVIIa injections, with dose ranging from 5 to 320 μg/kg. The FVII:C kinetic was fitted to a 2 compartment model, with continuous “endogenous perfusion” mimicking endogenous activity. Estimated clearance was 2.4 l/h (20% inter-individual variability and 9% inter-period variability). The volume of distribution at steady-state appeared to be significantly dose dependent: 78 ml/kg for doses ≤20 μg/kg and 88 ml/kg for doses >20 μg/kg respectively, with 16% inter-individual variability. The dose producing 50% of the maximum drop of INR was estimated to be 2.2 μg/kg. The model will be used to better define the dosage regimen for future clinical developments.